2021
DOI: 10.3389/fphys.2021.648399
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Attenuates Cardioprotective Effects of Glucagon-Like Peptide-1 Through Induction of Mitochondria Dysfunction via Inhibition of β-Arrestin-Signaling

Abstract: An increased vulnerability has been detected after ischemia/reperfusion injury in cardiomyocytes in diabetic patients. Glucagon-like peptide-1 (GLP-1) has been proven to have a notable cardioprotective effect in cardiomyocytes. However, in diabetic patients, the cardioprotective effects of GLP-1 are compromised, which is called GLP-1 resistance. β-arrestin is one of the two main downstream effectors of GLP-1 and β-arrestin signaling pathway exerts cardioprotective effects upon activation of GLP-1R. Our hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…However, the role of ARRB1 in mitochondrial function is still unclear. High glucose induces mitochondrial dysfunction by inhibiting ARRB signaling to attenuate the cardio-protective effects of glucagon-like peptide 1(GLP-1) [30]. Knockdown of ARRB1 inhibited isoproterenol-induced mitochondrial ROS production [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of ARRB1 in mitochondrial function is still unclear. High glucose induces mitochondrial dysfunction by inhibiting ARRB signaling to attenuate the cardio-protective effects of glucagon-like peptide 1(GLP-1) [30]. Knockdown of ARRB1 inhibited isoproterenol-induced mitochondrial ROS production [50].…”
Section: Discussionmentioning
confidence: 99%
“…ARRB1 has been identi ed as a critical regulator of glucose and energy homeostasis [29]. Pan et al found that high glucose attenuated the cardioprotective effects of glucagon-like peptide 1 through induction of mitochondrial dysfunction via inhibition of ARRB1 [30]. Nevertheless, ARRB1 has increased mitochondrial oxidative stress in cultured human cardiac broblasts [31].…”
Section: Introductionmentioning
confidence: 99%